2008
DOI: 10.1007/s10800-008-9623-2
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 5′-triphosphate incorporated poly(3,4-ethylenedioxythiophene) modified electrode: a bioactive platform with electroactivity, stability and biocompatibility

Abstract: Poly(3,4-ethylenedioxythiophene) (PEDOT) was potentiostatically polymerized onto gold electrode with adenosine 5 0 -triphosphate (ATP), an important biomolecule, as the counterion. Essential parameters to affect the impedance of the resultant polymer were studied in detail. Results show that 1.0 V, 0.1 M and 2.2 mC is the optimal deposition potential, dopant concentration and quantity of the passing charges, respectively. Surface topography was studied by AFM and the relationship between impedance and topograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…PEDOT coatings can be prepared by electrochemical polymerization in aqueous solution which allows the direct incorporation of water soluble anions [ 7 , 24 ]. Xiao and co-workers have developed an adenosine 5′-triphosphate (ATP) doped PEDOT for neural recording [ 25 ]. A silver nanograin incorporating a poly(3,4-ethylenedioxythiophene) (PEDOT) modified electrode for electrocatalytic sensing of hydrogen peroxide by simple electrochemical method was reported recently by Balamurugan and his co-workers [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…PEDOT coatings can be prepared by electrochemical polymerization in aqueous solution which allows the direct incorporation of water soluble anions [ 7 , 24 ]. Xiao and co-workers have developed an adenosine 5′-triphosphate (ATP) doped PEDOT for neural recording [ 25 ]. A silver nanograin incorporating a poly(3,4-ethylenedioxythiophene) (PEDOT) modified electrode for electrocatalytic sensing of hydrogen peroxide by simple electrochemical method was reported recently by Balamurugan and his co-workers [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of these negative effects, many research groups have studied possible surface modifications to increase the compatibility with in vitro and in vivo experiments. Many groups have shown that the deposition of electrically conductive polymers such as PPy, PDI‐Lys, or more recently PEDOT/ATP, provide increased stability and biocompatibility . Further research into composites containing carbon nanotubes shows increased conductivity and decreased impedance while maintaining biological compatibility .…”
Section: Conductivity and Photoconductivitymentioning
confidence: 99%
“…Despite the solubility limitations of EDOT some studies show successful incorporation of biomolecules using only aqueous solution of biomolecule and EDOT. 68,69 Asplund et al 68 showed that heparin, hyaluronic acid and fibrinogen could be used as counterions in the electropolymerization of PEDOT using only aqueous solution and no surfactants. The formed PEDOT:heparin had electrochemical performance similar to PEDOT:PSS and also PEDOT:HA showed similar impedance behaviour.…”
Section: Incorporation Of Biomolecules At Electro-polymerizationmentioning
confidence: 99%
“…Xiao et al 69 reported successful incorporation of adenosine 5 0triphosphate (ATP) into PEDOT from aqueous monomer ATP solution. ATP release from the film to solution was confirmed for the first two days whereafter it declined.…”
Section: Incorporation Of Biomolecules At Electro-polymerizationmentioning
confidence: 99%